Analysis of physical performance during a congested-fixture tournament in semiprofessional basketball players - Izquierdo Velasco, José María; Delgado Márquez, Elvira; Verde Rello, Zoraida; Redondo Castán, Juan Carlos (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The aim of our study was to determine the predictors of physical performance evaluated by the mean of acceleration capacity (10-m and 20-m sprint) and jumping ability (CMJ) during three consecutive days’ semiprofessional basketball tournament. For this, 24 male players (24,3±3,4 years) were monitored during the tournament to assess the percentage of maximal actions (PMA) and T and C concentrations. Test were conducted 24 h before the first game started, after the end of each of the 3 games and 24 h after the last game. The results showed that the decrease in the physical variables through the tournament can be predicted by the mean of a panel data model including the level of exertion evaluated both by perceived exertion load and C, CMJ models were the most significant (Within-R2 = 0,60 and Within-R2 = 0,54 respectively). Therefore, it is recommended the use of cortisol monitoring on testing the demands of exercise in these competitive contexts. In addition, results allow us to enlarge knowledge of the internal and external demands in basketball matches.